Evaluation of Habitat Suitability for Rhino (Rhinoceros unicornis) in Orang National Park Using Geo-Spatial Tools. (29th March 2011) - Sarma, Pranjit Kumar; Mipun, B. S.; Talukdar, Bibhab Kumar; Kumar, Rajeev; Basumatary, Ajit Kumar
Abstract : Orang National Park (Orang NP) is one of the important conservation areas in the Brahmaputra valley within North East India biogeographic zone covering an area of 78.8 km 2 . It is one of the prime habitats of one horned rhino ( Rhinoceros unicornis ) in its distribution range in south Asia. Satellite imagery of November 2008 was used to evaluate the rhino habitat pattern in the park. A habitat suitability model for one horned rhino was prepared using primary and secondary sources. Result indicates that out of total geographical area of the park 25.85% is covered by woodland. About 26.06% is covered by wet alluvial grassland and 17.97% is covered by dry savannah grassland. Similarly degraded grassland is covering 15.23% and eastern seasonal swamp forest is covering 1.72% of the park. About 8.22% of the park is covered by water body and 6.83% is covered by sandy area. The habitat suitability model for rhino shows that 25.13% of the park is most suitable habitat for rhino, 13.62% is moderately suitable and 61.23% is less suitable habitat for rhino in the park. This information will help the park managers to conserve rhino and its habitat in Orang NP.